The Current Status and Composition of Bio-Medical Waste Management in Narayani Hospital of Birgunj Metropolitan City - Shah, Pradip; Regmi , Praveen Kumar (Journal of Environment Sciences, 2025)
The biomedical waste generated during treatment, immunization of human or animals, diagnosis, laboratory activities from Narayani hospital and other medical center in the Birgunj Metropolitan City become a serious public and environmental concern. Therefore, the general objectives of the study are to identify the current status and practices of bio-medical waste management with specific objectives to find out the status and composition of bio-medical waste and to access the method of management in Narayani Hospital and other also. The simple random sampling technique used to collect data from Narayani hospital and 50 responses on the day of one week. The study showed total biomedical waste generation rate is 48kg/day and 0.16 kg/bed/day. Generally, generated biomedical waste were Vials, Syringe, Saline bottle, Gloves, Cardboard box, Plastic Wrapper, Intravenous Set and Cotton gauge. The result showed, there are 36 hospitals with 2500 beds in Metropolitan city from which 54.92 tons/ year of Intravenous set, 21.89 tons/year of Vials, 1.64 tons/year of plastic wrapper, 8.65 tons/year of Cotton gauge, 10.08 tons/year of syringe, 20.02 tons/year of saline bottles, 8.78 tons/year of gloves and 19.79 tons/year of Cardboard box generated from entire hospitals. Similarly, from entire hospital 0.43 tons/day, 3.00 tons/week, 13.02 tons/month and 156.19 tons/year of recyclable biomedical waste generated. In case of disposal and management approach 88 percent respondents to collect waste in dustbin and 12 percent in Polyethene bags. Hence, it concluded segregation, collection, transportation, storage, disposal and management practice of the biomedical waste was found satisfactory.